PENGEMBANGAN MEDIA INTERAKTIF IPA BERWAWASAN KEARIFAN LOKAL KALIMANTAN SELATAN UNTUK SISWA KELAS IV SEKOLAH DASAR - Ria Mayasari (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
The purpose of this study was to determine the feasibility of interactive IPA media based on local wisdom of South Kalimantan for fourth grade elementary school students. The development of this media follows the development steps according to Sugiyono (2015), namely: 1) potential and problems; 2) data collection; 3) product design; 4) design validation; 5) product revision I; 6) product trial; 7) product revision II; 8) trial use; 9) product revision; and 10) mass products. However, the development of this media has only reached the stage of product revision step I. The instruments used in this study were observation sheets, interview sheets, questionnaire sheets and validation sheets. The data analysis technique used is descriptive quantitative. The results show that the results of validation by material experts on media products are 89.3% with very feasible criteria, 90% of media validation results for media products with very feasible criteria and linguistic validation results for media products get a percentage of 83.3% with proper criteria.